Effects of ambulatory blood pressure monitoring on sleep in healthy, normotensive men and women - Gaffey, Allison E. (Blood Press Monit, 2021)
OBJECTIVES: To determine the effect of ambulatory blood pressure monitoring (ABPM) on sleep quality among healthy adults and to explore possible effect modification by demographic factors. METHODS: We examined data from 192 relatively healthy young (median age:31, 33% men, 18% with clinic BP >130/80 mmHg) participants in an observational study of sleep and arterial stiffness. Demographic and health questionnaires were completed at baseline. A wrist-based accelerometer was used to assess sleep for 7 consecutive nights, from which sleep duration, wakefulness after sleep onset (WASO), sleep fragmentation (physical restlessness), sleep midpoint, and sleep efficiency were estimated. ABPM was conducted for one 36-hour period, including 1 actigraphy night. RESULTS: Within-subject comparisons indicated WASO and fragmentation were higher, midpoint was later, and efficiency was lower on the ABPM night (Ps<0.001–0.038). Neither age nor sex moderated these associations. Among older adults, a later midpoint and greater fragmentation were observed with ABPM (Ps=0.002–0.010). There was also a main effect of sex: men demonstrated shorter sleep duration, greater WASO and fragmentation, and less efficiency than women (Ps=0.002–0.046). With ABPM, women had worse fragmentation and a later midpoint (Ps=0.002–0.049); for men, WASO and fragmentation were worse (Ps=0.003–0.023). Importantly, this study does not address whether the effect of wearing ABPM on sleep in turn affects BP during sleep. CONCLUSIONS: The present study demonstrates that ABPM modestly disturbs actigraphy-assessed sleep among healthy adults. Researchers and clinicians should consider the downstream effects of performing ABPM and whether these effects are more pronounced in those who typically experience sleep disturbance.